2018
DOI: 10.1208/s12248-018-0247-0
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Drug-Transporter Interactions in a 3D Microfluidic Renal Proximal Tubule on a Chip

Abstract: Drug-transporter interactions could impact renal drug clearance and should ideally be detected in early stages of drug development to avoid toxicity-related withdrawals in later stages. This requires reliable and robust assays for which current high-throughput screenings have, however, poor predictability. Kidney-on-a-chip platforms have the potential to improve predictability, but often lack compatibility with high-content detection platforms. Here, we combined conditionally immortalized proximal tubule epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 50 publications
0
56
0
Order By: Relevance
“…Coculturing of hRPTECs and endothelial cells was also shown to improve cell viability, mitochondrial activity, and sodium-dependent glucose reabsorption under flow conditions (Vedula et al, 2017). Immortalized human proximal tubule cells showed a high level of membrane polarization in a microplateformat MPS model, while retaining similar levels of P-gp and MRP activity and gene expression (Vriend et al, 2018). In one of the first proof-of-concept studies of renal MPS models, the activity of the efflux transporter P-gp was increased compared with static culture, shown by using the fluorescent probe substrate Calcein-AM, in the presence of the P-gp inhibitor verapamil.…”
Section: Drug Transporter Characterization In Mps Modelsmentioning
confidence: 97%
“…Coculturing of hRPTECs and endothelial cells was also shown to improve cell viability, mitochondrial activity, and sodium-dependent glucose reabsorption under flow conditions (Vedula et al, 2017). Immortalized human proximal tubule cells showed a high level of membrane polarization in a microplateformat MPS model, while retaining similar levels of P-gp and MRP activity and gene expression (Vriend et al, 2018). In one of the first proof-of-concept studies of renal MPS models, the activity of the efflux transporter P-gp was increased compared with static culture, shown by using the fluorescent probe substrate Calcein-AM, in the presence of the P-gp inhibitor verapamil.…”
Section: Drug Transporter Characterization In Mps Modelsmentioning
confidence: 97%
“…The most diffusely and appealing application of tubule-on -a-chip is drug-induced nephrotoxicity screening [134][135][136]. This technology was helpful to reproduce the in vivo cisplatin and gentamicin toxicity, demonstrating that the once-a-day bolus dosing method was less nephrotoxic than the continuous infusion method [137].…”
Section: Tubule-on-a-chipmentioning
confidence: 99%
“…This technology was helpful to reproduce the in vivo cisplatin and gentamicin toxicity, demonstrating that the once-a-day bolus dosing method was less nephrotoxic than the continuous infusion method [137]. Moreover, the combination of tubule-on -a-chip systems with innovative detection methods to analyze novel biomarkers specific for nephrotoxicity identifies this technology as a fully compatible platform with automation and high content screening equipment [134][135][136][137][138][139][140][141]. However, the goal standard in understanding nephrotoxicity is the integration of multiple cell types from different organs.…”
Section: Tubule-on-a-chipmentioning
confidence: 99%
“…Advances in microelectromechanical systems (MEMs) allowed researchers to apply microfluidics in cell and tissue cultures that resulted in the so-called Ryan et al (1994), Zhao et al (2017), Jenkinson et al (2012b) and Murphy et al (2017) Nki-2 organ-on-a-chip (Table 3). Vriend et al demonstrated that culturing ciPTEC-OAT1 in an OrganoPlate, a 3D platform consisting of 96 chips that provides fluid shear stress by placing the plate on a rocker platform, it was possible to create a high-throughput screening method compatible with advanced imaging techniques (Vriend et al 2018). Following a similar approach, Schutgens et al developed a new microfluidic in vitro system using kidney tubular epithelial organoids, or "tubuloids", derived from adult stem cells.…”
Section: Advanced In Vitro Modelsmentioning
confidence: 99%